(untitled) (Swiss Medical Weekly, 2024)
INTRODUCTION: During the first wave of the COVID-19 pandemic, increasingly strict restrictions were imposed on the activities of the Swiss population, with a peak from 21 March to 27 April 2020. Changes in trauma patterns during the pandemic and the lockdown have been described in various studies around the world, and highlight some particularly exposed groups of people. The objective of this study was to assess changes in trauma-related presentations to the emergency department (ED) during the first wave of the COVID-19 pandemic, as compared to the same period in the previous year, with a particular focus on vulnerable populations. MATERIALS AND METHODS: All trauma-related admissions to our ED in the first half of 2019 and 2020 were included. Patient demographics, trauma mechanism, affected body region, injury severity and discharge type were extracted from our hospital information system. Trauma subpopulations, such as interpersonal violence, self-inflicted trauma, geriatric trauma and sports-related trauma were analysed. RESULTS: A total of 5839 ED presentations were included in our study, of which 39.9% were female. Median age was 40 years (interquartile range: 27–60). In comparison to 2019, there was a 15.5% decrease in trauma-related ED presentations in the first half of 2020. This decrease was particularly marked in the 2-month March/April period, with a drop of 36.8%. In 2020, there was a reduction in injuries caused by falls of less than 3 metres or by mechanical force. There was a marked decrease in sports-related trauma and an increase in injuries related to pedal cycles. Geriatric trauma, self-harm and assault-related injuries remained stable. CONCLUSION: This study described changes in trauma patterns and highlighted populations at risk of trauma during the pandemic in Switzerland in the context of previous international studies.These results may contribute to resource management in a future pandemic.